All for One and One for All? An Existential Perspective on Family and Systems Work as a Form of Therapeutic Intervention (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
The desire to observe and work with the family as the primary unit in the individual’s social context has lead to the development of various family therapy methodologies that seem to be predicated on one or both of two theoretical formulations, the first of which is philosophical and the second scientific. This paper seeks to explore these formulations and in so doing elucidate an existential perspective on Family Therapy. Whilst at first glance the aim of supporting autonomy while preserving mutuality (Minuchin 1974) would appear to have an affinity with the existential psychotherapeutic approach the question still remains as to whether it is really possible or desirable to view the family as the type of structure that can be imbued with the laws of organisational dynamics without loosing empathy for its individual members and whether in reality it is therapeutic for the individual in crisis (often with the family itself) to remain both autonomous and embedded in any meaningful way?
Keywords: Cybernetics; Family Therapy; Systems Theory; Individuation; Relatedness.